Direct and indirect effects of the COVID-19 pandemic on children with cardiovascular disease - Zühlke, Liesl; Brown, Stephen; Cilliers, Antoinette; Hoosen, Ebrahim; Lawrenson, John; Ntsinjana, Hopewell (SA Heart Journal, 2020)
Coronavirus 2 (SARS-CoV-2) the causative agent of what we now know as “Coronavirus Disease 2019” (COVID-19), is the most serious global health crisis of our generation, with a significant and far-reaching impact upon health, economy, social cohesion and emotional and mental wellbeing. Although children do not bear the brunt of direct mortality, they are significantly affected in terms of morbidity and interruption to access, continuity and complexity of care, as well as the indirect social and financial effects impacting on their health outcomes. In this review we present some of the most recent data relevant to children with congenital and acquired heart disease, and consider some of the cardiac presentations noted. We discuss the necessary protections to staff in the echo and cardiac catherisation laboratories and present some general recommendations to general paediatricians and communities to ensure the continued health of our patients. Finally, we encourage ongoing registries and biorepositories and support clinical trials to ensure that children also receive new technologies and therapeutics as these become available.